(untitled) (Indian Journal of Arid Horticulture, 2025)
Kinnow mandarin is an important fruit crop of sub-tropical and hot arid region. It is being grown in about 6500 ha in western parts of Rajasthan where irrigation facilities are available. It is sour-sweet in taste and fruits are available during November to January months. The fruit is generally used for fresh consumption and juice preparation. The post harvest losses in kinnow fruits has been faced by growers because of improper marketing and processing. The under size fruits are not suitable as such for fresh consumption because of small size and low percentage of juice recovery. The selling price of such fruits is also low in the markets. Therefore, the under sized kinnow fruits can be properly utilized for value addition purpose. The small sized unmarketable kinnow fruits can be used for making juice and ready-to- serve drinks. The physico-chemical characters of under size and normal fruits and its post harvest utilization studies were carried out at CIAH, Bikaner during 2010-11.